The Impact of Foreign Direct Investment and Information and Communication Technology on Lesotho’s Economic Productivity - Megbowon, Ebenezer; Mulatu, Zerihun (Acta Universitatis Danubius. Œconomica, 2024)
Objective: To identify and investigate from a national perspective the variety of factors that could influence the achievement of Sustainable Development Goal with focus of goal 8.2 on economic productivity, the aim of this study is to empirically examine the impact of foreign direct investment and the development of information and communication technology on Lesotho’s economic productivity. Approach: In this study, the stationary analysis is performed by using Phillips–Perron and Augmented Dickey–Fuller unit root tests, Johansen cointegration technique, and vector error correction method for short-run dynamics and causality relationship determination among the studied variables and their respective relative impact on economic productivity in the long-term period. Time series data for the period 1990 to 2021 was utilized to achieve the objectives of this study. Results: Results from the analysis suggest that FDI increases economic productivity in Lesotho, whereas ICT reduces. Implication: The result underscores the importance of creating an attractive investment climate and implementing policies to encourage foreign investors. It also suggests a need for re-evaluation of ICT investment strategies and policy interventions tailored to Lesotho’s economic landscape. Addressing underlying structural issues or inefficiencies in ICT utilization may require targeted interventions such as enhancing digital literacy, improving technology infrastructure, or fostering a conducive business environment for ICT adoption.